FINANCIAL RESOURCE MANAGEMENT AND THEORETICAL FOUNDATIONS OF ACCOUNTING IN HIGHER EDUCATION INSTITUTIONS - Kurbanov Jaloladdin Yuldashbaevich (American Journals, 2025)
This scientific work explores the formation of financial resources in higher education institutions, their efficient utilization, and the theoretical foundations of accounting. The study examines the structure of revenues and expenses, the movement of budgetary and extrabudgetary funds, principles of accounting, and the process of preparing financial statements. Additionally, theoretical perspectives on enhancing the effectiveness of financial management in higher education institutions, implementing digital technologies, and aligning accounting practices with international standards are analyzed. The research findings have practical significance for ensuring the financial stability of educational institutions and improving financial management systems.
Keywords: Higher education institution, financial resources, accounting, revenues and expenses, budgetary and extrabudgetary funds, financial management, international accounting standards.